Comparative analysis of adhesive remnant index of orthodontic adhesive systems - Santos, Larissa Kelly; Rocha, Hugo Ramos; Barroso, Anna Carollina Pereira; Otoni, Rejane Pereira; Santos, Carolina Carvalho de Oliveira; Fonseca-Silva, Thiago (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2022)
Introduction: At the end of orthodontic treatment, enamel fractures and cracks are pointed out as potential risks related to the procedures for removing fixed appliances bonding to teeth.  Aim of the study: The objective of the present study was to analyze comparatively residual adhesive index of different adhesive systems used in Orthodontics for bonding brackets on the dental surface.  Materials and Methods: The present in vitro study was performed with 120 healthy human extracted premolars randomly divided into two groups to receive the bonding of steel and ceramic brackets. Then, the teeth were divided into six subgroups according to adhesive system used: G1: Orthocem®; G2: Orthocem® + Ambar universal® adhesive; G3: Orthobond Plus®; G4: Biofix®; G5: Transbond XT® and G6: Ortholink VLC®. The analysis of the residual adhesive index was performed using a microscope under 20x magnification after removing the brackets. Data were analyzed with Mann-Whitney test. The level of statistical significance was set at P < 0.05.  Results and Conclusions: The score of the most prevalent adhesive index in steel brackets group was 2, while in ceramic brackets group was 3. Comparatively, Orthobond Plus®, Biofix® and Ortholink VLC® showed better performance of adhesive remnant index than Orthocem® + Ambar® in steel brackets group. For ceramic brackets, Biofix® and Transbond XT® adhesives performed better than Orthobond Plus®.
Keywords: Composite resin; Orthodontics; Dental enamel; Adhesion